Autonomous mobility on demand: from case studies to standardized evaluation - Alotaibi, Ebtehal T.; Alhuzaymi, Thaqal M.; Herrmann, J. Michael (Frontiers in Future Transportation, 2023)
We present an overview of ten case studies of autonomous mobility on demand (AMoD) transportation systems, which are based on realistic data from different urban contexts. Comparing AMoD systems with conventionally driven vehicles (CDV), the limits of reduction of vehicles, the cutting-back of parking spaces, and the increase of empty miles are investigated. As a result of introducing a shared fleet of autonomous vehicles (AV), the analysis demonstrated that 88% to 93% of CDV are not required to meet realistic requirements. Parking spaces can be reduced by 83% to 97%, while empty miles could be increased by 6% to 15%. Nonetheless, fleet dispatching techniques that use the advanced optimization algorithms can reduce the ratio of empty miles by as much as 40%. Consequently, we propose a standard procedure for conducting intelligent transportation system studies (ITS) that can assist in the planning of traffic on urban environments at operational, tactical, and strategic levels. Furthermore, the case studies enabled us to design an Intelligent Transportation System Readiness Level (ITS-RL) scale to assess the realism of case studies, facilitate risk assessment, and provide guidance on how to incorporate AMoD system within a local context.